Effects of a circuit training program in improving cardiorespiratory fitness, upper extremity strength, and agility in paraplegic subjects - Francesco Tafuri; Rosabel Martinez-Roig; Khoiril Anam; Nugroho Susanto; Hendra Setyawan; Emma Saraiello; Francesca Latino (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Exercise and sports may play a crucial role for individuals with disabilities due to their restricted levels of physical activity. Among people with disabilities, engaging in sports and exercise has the potential to notably enhance their physical and physiological functioning. Consequently, the aim of this research was to investigate the effects of a circuit training program on the cardiorespiratory fitness, musculoskeletal strength, and agility of wheelchair users. The study involved 28 participants with paraplegia as a result of spinal cord injury, aged between 19 and 40 years, who were divided into two groups: an experimental group (EG, n = 14) participating in circuit training, and a control group (CG, n = 14) undergoing aerobic upper-body exercise exclusively. All subjects took part in the wheelchair yo-yo test and hand grip test, both conducted at the commencement and conclusion of the training period. The results displayed a significant Time x Group interaction for both variables, indicating a substantial improvement in the intervention group (p < 0.001), while no significant changes were observed in the control group. Therefore, the findings suggest that incorporating circuit training into the daily routine of wheelchair users has a positive impact on their overall well-being, ultimately enhancing their quality of life.